1997
DOI: 10.1029/96tc03935
|View full text |Cite
|
Sign up to set email alerts
|

Successive orthogonal and oblique extension episodes in a rift zone: Laboratory experiments with application to the Ethiopian Rift

Abstract: Abstract. Small-scale modeling was performed to examine the effects of the superposition of two successive extensional phases from orthogonal to oblique (type I) and from oblique to orthogonal (type 2). In both the type 1 and type 2 models, faults produced during the first stage strongly control fault development during the second stage. In type 1 models, the oblique faults developed during the second oblique phase are confined within a first-phase graben, whereas in type 2 models the oblique faults, produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
128
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(143 citation statements)
references
References 42 publications
8
128
0
2
Order By: Relevance
“…12). Bonini et al (1997) also come to this conclusion based on their model results, but these authors concluded that the transtension persists to the present day. In our interpretation, the duration of this phase of rifting is too short to accumulate measurable block rotations observable by palaeomagnetic investigations.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…12). Bonini et al (1997) also come to this conclusion based on their model results, but these authors concluded that the transtension persists to the present day. In our interpretation, the duration of this phase of rifting is too short to accumulate measurable block rotations observable by palaeomagnetic investigations.…”
Section: Discussionmentioning
confidence: 92%
“…The obliquity of Miocene border faults and Quaternary faults in the Wonji belt led Bonini et al (1997) to propose a model of oblique extension along the border faults after a change in extension direction, which probably occurred at around 3.5 Ma to accommodate along-axis propagation in the Gulf of Aden (Wolfenden et al 2004). The Quaternary development, therefore, of the Wonji belt (our magmatic segments) has been attributed to oblique extension, with a left-lateral component of motion along the rift floor (e.g.…”
Section: Magmatic Segmentsmentioning
confidence: 99%
“…The distribution, kinematics, and estimated age of fault populations suggest that deformation in the Main Ethiopian Rift north of 8.5°N migrated to the center of the rift sometime in the interval 6.6-3 Ma, with an associated change from N130°E-directed extension to N105°E-directed extension (Bonini et al, 1997;Boccaletti et al, 1998;Wolfenden et al, 2004). Opening models of the East African Rift based on global positioning system (GPS) data and earthquake focal mechanisms constrain the current extension direction in the Main Ethiopian Rift to between N95°E and N110°E at rates of 4-7 mm/yr (Bilham et al, 1999;Fernandes et al, 2004;Calais et al, 2006;Stamps et al, 2008).…”
Section: The Ethiopia Afar Geoscientifi C Lithospheric Experiments (Eamentioning
confidence: 96%
“…The obliquity of Miocene border faults and Quaternary faults in the Wonji belt led Bonini et al (1997) to propose a model of oblique extension along the border faults after a change in extension direction, which probably occurred at around 3.5 Ma to accommodate along-axis propagation in the western Gulf of Aden (Wolfenden et al, 2004;Audin et al, 2004). The magmatic segments of the northern Main Ethiopian Rift have been attributed to oblique extension, with a left-lateral component of motion along the rift floor (e.g., Mohr, 1968;Boccaletti et al, 1998).…”
Section: Magmatic Segments In the Northern Mer And Southern Red Sea Rmentioning
confidence: 99%